Impedancemetry vs. anthropometry in the prediction of body adiposity and obesity diagnosis - Abulmeaty, Mahmoud Mustafa Ali; Almajwal, Ali Madi; Alsaif, Mohammed Abdullah; Hassan, Heba Mohammed Zaher; Almansour, Sarah Khalid (Progress in Nutrition, 2016)
Background and aim:  Many Bioelectrical impedance analysis (BIA)-based parameters require clinical evaluation. This study was performed to evaluate the relationships between some BIA-based parameters and anthropometric parameters for obesity diagnosis. Methodology: A total of 358 male subjects aged from 19-63 were enrolled in a cross sectional study. The anthropometric measures included weight, height, body mass index (BMI), waist circumference, hip circumference and waist hip ratio. InBody 720 was used to calculate the fat mass, fat mass index (FMI), percent body fat, visceral fat area (VFA), and other related measures. Results: Fat mass index had stronger positive correlation with BMI than percent body fat (r=0.9161 vs. r=0.7516, P